1998
DOI: 10.1093/jac/41.2.253
|View full text |Cite
|
Sign up to set email alerts
|

Effects of cefixime or co-amoxiclav treatment on nasopharyngeal carriage of Streptococcus pneumoniae and Haemophilus influenzae in children with acute otitis media

Abstract: A multicentre, open-label, randomized study was performed in 501 out-patients with acute otitis media, aged 6-36 months, to study the impact of treatment with either cefixime suspension 8 mg/kg/day bd or co-amoxiclav suspension 80 mg/kg/day tds for 10 days on nasopharyngeal carriage of Streptococcus pneumoniae and Haemophilus influenzae. Of 426 patients with nasopharyngeal cultures at entry to the trial, end of treatment and at follow-up visit (35 days after inclusion), significant changes in carriage of S. pn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
39
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(41 citation statements)
references
References 15 publications
2
39
0
Order By: Relevance
“…Antibiotic use is known to be a major risk factor for the occurrence of resistant bacteria. Several studies have revealed the potential impact of antibiotic use on the increase in the rate of nasopharyngeal carriage of resistant H. influenzae isolates in children (3,6,28,29,40). In our study, the percentage of children who were under treatment for common infantile inflammatory diseases did not differ between the summer and the winter.…”
Section: Discussionmentioning
confidence: 40%
“…Antibiotic use is known to be a major risk factor for the occurrence of resistant bacteria. Several studies have revealed the potential impact of antibiotic use on the increase in the rate of nasopharyngeal carriage of resistant H. influenzae isolates in children (3,6,28,29,40). In our study, the percentage of children who were under treatment for common infantile inflammatory diseases did not differ between the summer and the winter.…”
Section: Discussionmentioning
confidence: 40%
“…In H. influenzae, it is the production of TEM-type ␤-lactamase that is the most frequent. Unlike in other countries, where the prevalence of ␤-lactamase is low (lower than 10%) (17,26), in France the frequency of ␤-lactamase-producing strains is high, over 35%, in particular for strains isolated from the nasopharynx or those causing acute otitis media (6,13,27).…”
Section: Discussionmentioning
confidence: 89%
“…These invasive diseases have decreased sharply since the generalization of anti-Haemophilus b (anti-Hib) vaccination (22, 37). Noncapsulated strains frequently cause acute otitis media in children (6,20,29,32). H. influenzae is often part of the nasopharynx flora and is frequently found in the upper respiratory tract of healthy children, with reported carriage rates of up to 60% (12,17,23,32).…”
mentioning
confidence: 99%
“…It has frequently been clinically noted that antimicrobial agents often fail to eradicate bacteria from the nasopharynx, making colonization a more challenging target than treatment of invasive disease (18,19,(21)(22)(23)26). The reason for this is unknown, but it could suggest that biofilm formation is an important aspect of pneumococcal carriage.…”
mentioning
confidence: 99%